2021
DOI: 10.1177/03000605211041275
|View full text |Cite
|
Sign up to set email alerts
|

Chronic venous disease patients show increased IRS-4 expression in the great saphenous vein wall

Abstract: Objectives Chronic venous disease (CVeD) is a multifactorial and debilitating condition that has a high prevalence in Western countries and an important associated socioeconomic burden. Varicose veins (VVs) are the most common manifestations of CVeD. Pathologically, many morphological and functional changes have been described in VVs, which most notably affect venous wall integrity. Previous studies have found several molecular alterations that negatively affect normal cell signaling pathways. Insulin receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Finally, immunohistochemical analysis shows that IL-10 is expressed in 6 pancreatic cancer patients, whereas 31.7% present negative expression for this cy The median survival for patients with pancreatic cancer and negative tissue expre IL-10 was 4 (4-7) months. However, in the case of patients with low-medium exp it was 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) months, increasing to 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) months in patients with a high exp (Figure 2B). Global comparisons showed that the significance value was p < 0.001 * a hazard ratio of 0.265 and a 95% confidence interval [0.142-0.500] in patients w expressions of IL-10.…”
Section: Aif-1 Il-12a and Il-18 Are Directly Related To Pancreatic Ca...mentioning
confidence: 94%
See 1 more Smart Citation
“…Finally, immunohistochemical analysis shows that IL-10 is expressed in 6 pancreatic cancer patients, whereas 31.7% present negative expression for this cy The median survival for patients with pancreatic cancer and negative tissue expre IL-10 was 4 (4-7) months. However, in the case of patients with low-medium exp it was 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) months, increasing to 24 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) months in patients with a high exp (Figure 2B). Global comparisons showed that the significance value was p < 0.001 * a hazard ratio of 0.265 and a 95% confidence interval [0.142-0.500] in patients w expressions of IL-10.…”
Section: Aif-1 Il-12a and Il-18 Are Directly Related To Pancreatic Ca...mentioning
confidence: 94%
“…When the mean proportion of the labeled sample was greater than or equivalent to 5% of the entire sample, the individuals were categorized as positive. As previously described in previous works [24], this was accomplished by computing the overall percentage of marked tissue in each microscope field to produce an average of the research sample. Two researchers worked independently to observe and quantify the samples.…”
Section: Histopathological Evaluationmentioning
confidence: 99%
“…(1) To synthesize complementary DNA (cDNA) via reverse transcription, RNA samples were diluted to 50 ng/µL; then, 4 µL of diluted RNA was mixed with 4 µL of oligo-dT solution at 0.25 µg/µL (Thermo Fisher Scientific A., Waltham, MA, USA) and incubated at 65 • C for 10 min in a dry bath (AccuBlock™, Labnet International Inc., Edison, NJ, USA) to denature the RNA. (2) Next, the samples were put on ice, and 10 µL of a reverse transcription mixture was added to each sample in agreement with established protocols [18]. (3) Reverse transcription was performed to synthesize cDNA using a G-Storm GS1 thermocycler (G-Storm, Somerset, UK) at 37 • C for 1 h and 15 min, 70 • C for 15 min (leading to denaturation of the reverse transcriptase enzyme) and then a gradual decrease to 4 • C. (4) To verify the absence of genomic DNA contamination in the total RNA samples, negative control samples were run in parallel; in these samples, M-MLV RT was replaced with DNase-and RNase-free water.…”
Section: Analysis Of Gene Expression Using Qrt-pcrmentioning
confidence: 99%
“…( 6) qPCR was performed to quantify the levels of cDNA of our genes of interest. ( 7) Specific primers were designed de novo for the studied genes (Table 3) using Primer-BLAST (National Center for Biotechnology Information, Bethesda, MD, USA) and AutoDimer [18]. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) gene was used to normalize the results.…”
Section: Analysis Of Gene Expression Using Qrt-pcrmentioning
confidence: 99%
“…Pathophysiologically, CVeD is characterized by an ambulatory venous hypertension, which affects the venous valves, compromising the venous return, frequently in the lower limbs [ 11 , 12 ]. The persistent hypertension is a major source of local and systemic inflammation, leading to an increase in oxidative stress, endothelial dysfunction, chronic hypoxia, matrix remodeling and so on [ 13 , 14 , 15 , 16 ]. Eventually, in advanced stages of the disease, skin changes such as pigmentation, lipodermatosclerosis and ulcerations can be observed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%